Presenting an Organizational Training Model for Enhancing Policy-Making Capacities in the Agricultural Jihad Organization - Kaki , Fatemeh; Rudgar Nezhad , Forugh; Moghimi , Seyedeh Fataneh (Management Strategies and Engineering Sciences, 2025)
Training and development of human resources within the human resource management system not only play a crucial role in increasing employees’ knowledge and skills but also contribute to improving organizational efficiency and effectiveness and adapting to environmental pressures. The primary reason for developing employees’ knowledge and skills lies in job requirements and addressing performance-related challenges. This study aims to present an organizational training model for enhancing policy-making capacities in the Agricultural Jihad Organization using a grounded theory approach based on three stages of coding: open, axial, and selective. The statistical population includes all managers and experts of the Agricultural Jihad Organization. Given the qualitative nature of the study, the sampling method was purposive and conducted using the snowball technique, allowing for in-depth investigation. Data collection was carried out through interviews with 17 experts and experienced professionals in the Agricultural Jihad Organization and the field of policy-making, reaching theoretical saturation. The study’s findings identified 29 influential components categorized into causal conditions (6 components), contextual conditions (4 components), intervening conditions (4 components), strategies for implementing organizational training (8 components), and its outcomes (6 components), all revolving around the central phenomenon of organizational training.